Men In Black - Sonnenfeld, Barry, 1953-; Jones, Tommy Lee.; Will Smith; Linda Fiorentino; Vincent D'Onofrio; Rip Torn; Tony Shalhoub; Tony Shalhoub (USA Automat Pictures, 1997)
Two men who keep an eye on aliens in New York City must try to save the world after the aliens threaten to blow it up.
Protecting the earth from the scum of the universe
Lowell Cunningham
Languages : English, German, French
Subtitles : Turkish, English, French, German, Dutch, Polish, Arabic, Bulgarian, Czech, Danish, Finnish, Greek, Hebrew, Hindi, Hungarian, Icelandic, Norwegian, Swedish
Keywords: Action; Comedy; SciFi